Health effects of ground water fluoride contamination in Bankura district of West Bengal, India. - PRITHVIRAJ KARAK (International Journal of Pharma and Bio Sciences, 2017)
India is a subcontinent country with large amount of resources, though many places in India people uses ground water as only the sources for drinking and domestic purpose. But ground water is not safe in most of the places. Arsenic and Fluoride are the major concern of ground water pollution in these days. The Indian Ministry of Water Resources informs that several districts of nine states (i.e., Bihar, Haryana, Jharkhand, Karnataka, Maharashtra, Madhya Pradesh, Orissa, Tamil Nadu and Uttar Pradesh) of India are affected by high Fluoride concentrations (greater than 1 mg/l) in groundwater. Fluoride has beneficial effects on teeth at low concentrations of 1mg/l by preventing and reducing the tooth decay. Fluorosis is a common disorder it occurs due to entry of fluoride in the body, which affects every organ, tissue, cells in the body, and results in health complaints having overlapping manifestations with several other diseases like gouts and osteoporosis. In short, it also causes dental fluorosis, musculo-skeletal fluorosis. Fluoride damages the Pineal Gland and affects the reproductive systems and intelligence.